BENTUK PERBUATAN MELAWAN HUKUM AKIBAT PEMBIARAN TERHADAP TIDAK LAYAKNYA ALAT TRANSPORTASI KAPAL YANG MENGALAMI KECELAKAAN DI TINJAU DARI ASPEK HUKUM PERDATA POSITIF - Renreng, M. Ridha (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTWhereas Article 1365 of the Civil Code states that any unlawful act, which carries harm to another person, requires a person who, for whose fault, issues the loss, compensates for such loss. That there are 3 (three) categories of unlawful acts, namely: Unlawful acts because of intent; Unlawful acts without error; The law against negligence. Regarding the form of counterfeiting against the unlawful vessel of the ship's shipwreck, it requires an interpretation to find the answer whether it is in the category of intent or legal action without error or act against the law because of negligence. The authors argue that since it has been previously known by the businessman of the ship's transfor- mation tool and the continued operation of the ship's transportation means it is a category of unlawful acts of intent. Therefore, the accountability of the action against the law according to the positive civil law as Article 1365 of the Civil Code shall be imposed on the damnant of such losses in this case that the loss is imposed on the vessel's transportation entrepreneurs because the act of omitting the tranfortation equipment of the vessel which has remained in operation, that the ship's transfotation equipment is not feasible operation and remains operated. In the Ordinance of 1935 ships has been specified on the requirements of the vessel's eligibility in making the voyage as well as licensing requirements issued by the Indonesian Bureau of Classification or issued by the government through the Syahbandar Office and the Head of the Office of the Transportation Service. For and to be safe in the voyage, the surface water vessels shall be equipped with letters of vessels which are guarantees for the eligibility of the vessel to sail in accordance with the requirements specified in the Orders of 1935 ships and the Ordinance of 1927 inland vessels as well as the rules of their operation . A ship is said to be worthy of a screen to transport passengers and / or goods if it has a certificate of perfection. This is mentioned in Article 6 paragraph (1) and (3) Ordinance of ships 1935.Â Keywords Â : Unlawful Actions, Losses Resulting from Omission and Negligence